Predictors of poor glycemic control among diabetic patients in Al-Madinah diabetic centre, Saudi Arabia - Almutairi, Mansour A. (2013)
Poor glycemic control is a major public health problem. In Saudi Arabia, the incidence of poor glycemic control was high among patients with diabetes mellitus. Good glycemic control is a major objective for the prevention or postponement of long-term complications from diabetes. Marker of diabetes control is the glycosylated hemoglobin A1c (HbA1c). The American Diabetes Association (ADA) has designated an HbA1c level of <7% as a goal for optimal blood glucose control. A cross sectional study was conducted to determine the predictors of poor glycemic control among ambulatory type 2 diabetes patients who were registered in the Al-Madinah Diabetic Centre, were at least 20 years of age, and had been diagnosed with diabetes for at least three months. A total of respondent were selected using systematic random sampling technique. The data were collected from 21st February 2010 to 21st May 2010 using a self-administered, pre-tested questionnaire. The data on HbA1c level were collected from the patients’ files because all the diabetic patients must have their HbA1c level checked at interval regular visit, every three or, 6 months or yearly. Poor glycemic control was defined as when HbA1c value is 7% or more for the past three month. The response rate was 92%. Among the respondents, the overall percentage of poor glycemic control was 76%. The percentage of patients with poor glycemic control was highest among males, aged 60 years and older, who have no formal education, no job, low income, a positive family history of diabetes and those with oral hypoglycemic agent and respondents with one or more complications. In addition, these patients were diagnosed at age 40 years and above and had diabetes for 7 years and longer, with low levels of physical activity, obesity, and abnormal caloric intake. The glycemic control were significantly associated with family history of diabetes, duration of diabetes mellitus, type of diabetic management and number of diabetic complications p<0.05). However, in the logistic regression analysis, the predictors of poor glycemic control were only positive family history of diabetes (OR=3.45, 95% CI: 1.29-9.18) and on oral hypoglycemic agents (OR=78.14, 95% CI= 8.88-687.69), and on insulin/combination treatment (OR=37.57, 95% CI: 4.07-346.55) than diet alone. This rather high proportion of poor glycemic control implies the need for the Diabetic Centre to make an effort to develop continuing educational programs that emphasize lifestyle modification and the importance of adherence to a treatment regimen for glycemic control among diabetic patients. Keywords: Poor glycemic control, Diabetes Mellitus, Obesity, Physical activities, Diabetic Centre.